2017
DOI: 10.1111/irel.12184
|View full text |Cite
|
Sign up to set email alerts
|

Do Changes in Regulation Affect Temporary Agency Workers’ Job Satisfaction?

Abstract: Standard-Nutzungsbedingungen:Die Dokumente auf EconStor dürfen zu eigenen wissenschaftlichen Zwecken und zum Privatgebrauch gespeichert und kopiert werden.Sie dürfen die Dokumente nicht für öffentliche oder kommerzielle Zwecke vervielfältigen, öffentlich ausstellen, öffentlich zugänglich machen, vertreiben oder anderweitig nutzen.Sofern die Verfasser die Dokumente unter Open-Content-Lizenzen (insbesondere CC-Lizenzen) zur Verfügung gestellt haben sollten, gelten abweichend von diesen Nutzungsbedingungen die in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 63 publications
0
9
0
Order By: Relevance
“…The same kind of analysis of allocation on the labor market can be carried out within employees, looking at public‐ versus private‐sector jobs (Luechinger et al ., ), part‐time versus full‐time jobs (Booth and Van Ours, ), and temporary versus permanent work (Busk et al ., ). Moving away from simple binary comparisons of this type, we can consider the choice of different occupations and industries.…”
Section: Some Uses Of Well‐being Datamentioning
confidence: 97%
“…The same kind of analysis of allocation on the labor market can be carried out within employees, looking at public‐ versus private‐sector jobs (Luechinger et al ., ), part‐time versus full‐time jobs (Booth and Van Ours, ), and temporary versus permanent work (Busk et al ., ). Moving away from simple binary comparisons of this type, we can consider the choice of different occupations and industries.…”
Section: Some Uses Of Well‐being Datamentioning
confidence: 97%
“…In fact, the hidden costs perspective has received mixed evidence mainly because temporary workers are far from being a homogeneous group ( Gracia et al, 2011 ). Globally, more positive outcomes were observed for fixed-term, longer duration, qualification-matching, high wage, and voluntarily chosen temporary contracts (i.e., for compensated and autonomous temporary workers), whereas negative outcomes were more prevalent for agency and casual work contracts, chosen under constraint, with shorter duration, low paid, and matching little the qualifications (i.e., for low-compensated /low-autonomy temporary workers) ( Busk et al, 2017 ; Campbell, 2004 ; Chambel & Castanheira, 2007 ; Dawson et al, 2017 ; De Cuyper & De Witte, 2007 ; Feldman et al, 1995 ; Krausz, 2000 ).…”
Section: Examining the Roles Of Autonomy Compensations And Ingroup Id...mentioning
confidence: 99%
“…This situation illustrates that policy measures are likewise important beyond work design concepts. In this respect Busk et al (2015) [ 90 ] pointed out that policy regulations also have an effect on job insecurity and job satisfaction of TA workers. In their study, they showed that the deregulation of TAW in Germany in the early 2000s led to lower job satisfaction among male TA workers.…”
Section: Conclusion For Practical and Policy Implicationsmentioning
confidence: 99%